Smart spending : a young consumer's guide - Schmitt, Lois (Scribner, 1989)
Offers advice on how to recognize and avoid consumer traps. Case studies discuss misleading advertising, consumer fraud, mail order problems, refund policies, product safety, food poisoning, fad diets, money management, and effective complaining.